Physical properties of turmeric (Curcuma longa L.) - T John Zachariah, T Anand, S Balasubramanian, A M Mohite, K K Singh (Journal of Spices and Aromatic Crops, 2012)
Turmeric (Curcuma longa) rhizome (var. IISR Alleppey Supreme) sample was divided into three grades (I: 25–35 mm, II: 35–45 mm, III: 45–55 mm) according to its major dimension to study its physical properties. The average values of geometric property viz., length (30.38–50.60 mm), breadth (9.77–10.64 mm), thickness (5.18–6.44 mm), arithmetic mean diameter (15.82–21.91 mm), geometric mean diameter (12.77–13.76 mm), square mean diameter (24.24–28.58 mm), equivalent diameter (17.61–21.41 mm), sphericity (0.27–0.42), aspect ratio (0.20–0.35), unit volume (1641–2901 mm3), surface area (771–1265 mm2) and shape factor (1.63–1.77) for grades I, II & III are reported. The gravimetric property viz., bulk density (260–348 kg/m3), true density (1341–1354 kg/m3) and porosity (74.53–80.93%), and frictional property viz., angle of repose (37.57–38.90°) and coefficient of friction with respect to different surface viz., aluminum sheet, mild steel sheet and plywood sheet for grades I, II and III were found to range between of 0.69–0.81, 0.84–0.94, 0.80–0.86, respectively.